POTENSI NON-DEBT TAX SHIELD DALAM MEMITIGASI PRAKTIK MANAJEMEN LABA - Sinurat, Fransiska Fenny Liliani; Destriana, Nicken (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study investigates the practice of earnings management, a topic of significant interest due to its reflection on managerial behavior in financial reporting. Earnings management involves manipulating reported earnings to present a desired financial picture. This research aims to uncover empirical evidence regarding the impact of non-debt tax shield, profitability, firm size, leverage, growth, and board of directors on earnings management within consumer cyclical and non-cyclical companies. The study focuses on consumer cyclical companies listed on the Indonesia Stock Exchange from 2020 to 2022. Using a judgment sampling method with four criteria, 151 companies were selected. Multiple regression analysis was employed to test the hypotheses. The findings indicate that non-debt tax shield and company size negatively influence earnings management, while profitability and growth positively affect it. However, leverage and the board of directors show no significant impact on earnings management.